THE INFLUENCE OF ADHERENCE TO TREATMENT ON MYOCARDIAL DYSFUNCTION IN ELDERLY AND SENILE PATIENTS WITH ISCHEMIC HEART DISEASE AND HEART FAILURE - Iu. V. Nikishchenkova; V. S. Nikiforov (Архивъ внутренней медицины)
The aim of the study was to study the influence of adherence to treatment on myocardial dysfunction in elderly and senile patients with ischemic heart disease (IHD) and chronic heart failure (CHF).Material and methods. The study included 86 patients with ischemic heart disease (CHD) of older age groups admitted to  hospital treatment because of the progression of CHF: 21 patients — 65 to 74 years, 65 patients — 75 to 89 years. A standard clinical  study, echocardiography with global longitudinal strain assessment (GLS), and a Morisky-Green test were performed.Results. It is established that in the group of persons of senile age  there is a lower adherence to treatment and more pronounced  structural and functional changes in the myocardium. The following  correlations were revealed: total score of the Morisky-Green test  with the left ventricular end-diastolic volume (r = -0.33, p <0.05), with the E/e’ (r = -0.37, p <0.05), with GLS (r = 0.53).Conclusion. The findings indicate a lower adherence of the senile patients on treatment of IHD and CHF in comparison with the  elderly. Low adherence to therapy, as well as postinfarction  cardiosclerosis, can apparently be considered as one of the factors contributing to the progression of myocardial dysfunction.